A novel synthesis of aurones: Their in vitro anticancer activity against breast cancer cell lines and effect on cell cycle, apoptosis and mitochondrial membrane potential - Hai Chen; Xiao-Dong Qi; Ping Qiu (Bangladesh Pharmacological Society, 2014)
A novel method for the synthesis of aurones from benzofuran-3(2H)-one by condensation with aromatic aldehydes is described. The anticancer activity of the synthesized compounds was evaluated by MTT assay and among the series of 15 compounds, (Z)-2-(4-methylbenzylidene) benzofuran-3(2H)-one (3e) and (Z)-2-(4-chlorobenzylidene) benzofuran-3(2H)-one (3f) were found to be most promising inhibitors against two breast cancer cell lines MDA-MB-231 and MCF-7. Further, the mechanism of action of these two compounds (3e and 3f) was studied by evaluating their effect on the cell cycle phase distribution, apoptosis induction by Hoechst staining as well as mitochondrial membrane potential loss using flow cytometry. The two compounds exhibited a time-dependent cell cycle arrest at G0/G1 phase. The two compounds induced a potent apoptotic effect in MCF-7 cancer cells showing chromatin condensation or dense staining fragmentation called apoptotic bodies, which implied an early apoptotic event. These two compounds also induced a potent loss in mitochondrial membrane potential.